Growth, productivity and economics of coral-432 (Indian mustard hybrid) under different cropping systems - S S Rathore; Kapila Shekhawat; Amit Meena; Dhiraj Singh (Journal of Oilseed Brassica, 2026)
An experiment was conducted on the performance of Indian mustard hybrid Coral-432 under semi-aridconditions during the 2010-11 and 2011-12 Rabi season at ICAR-Directorate of Rapeseed-MustardResearch (DRMR), Research Farm, Bharatpur, Rajasthan, India. Of the seven cropping systems(groundnut-mustard, cotton- mustard, soybean-mustard, pearl millet-mustard, sesame-mustard, cluster beanmustard,and fallow-mustard) tested, maximum growth rates at 30-60 days after sowing (DAS), 60-90 DAS,and 90 DAS to harvest, respectively, were obtained under sesame-mustard, fallow-mustard, and pearl milletmustardcropping systems. Among the yield attributes, the maximum number of primary branches, numbersof siliqua and 1000-seed weight were obtained under sesame-mustard, cluster bean-mustard, and fallow–mustard, respectively. Number of secondary branches per plant, number of seeds per siliquae and siliquaelength were maximum under the pearl milletmustard cropping system. Maximum seed yield per hectare wasobtained under the sesame-mustard cropping system.